1998
DOI: 10.1142/s0192415x98000257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Ginseng on Blood Pressure in Patients with Essential Hypertension and White Coat Hypertension

Abstract: The objective of this study is to evaluate the changes of diurnal blood pressure pattern after 8 weeks of red ginseng medication (4.5 g/day) by 24 hour ambulatory blood pressure monitoring. In 26 subjects with essential hypertension, 24 hour mean systolic blood pressure decreased significantly (p = 0.03) while diastolic blood pressure only showed a tendency of decline (p = 0.17). The decrease in pressures were observed at daytime (8 A.M.-6 P.M.) and dawn (5 A.M.-7 A.M.). In 8 subjects with white coat hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 10 publications
3
52
0
2
Order By: Relevance
“…16 As well, an 8-week nonrandomized trial demonstrated that 4.5 g/day of the natural KRG root significantly decreased BP in hypertensive individuals. 35 Furthermore, in a nonrandomized trial with young, normotensive adults, an aqueous extract of KRG root at a mean dose of 610 mg significantly decreased BP at 45, 60, and 75 minutes after intake. 34 Thus, although studies on ginseng and BP exist, the use of extracts and nonrandomized designs was common, which precluded an accurate assessment of efficacy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…16 As well, an 8-week nonrandomized trial demonstrated that 4.5 g/day of the natural KRG root significantly decreased BP in hypertensive individuals. 35 Furthermore, in a nonrandomized trial with young, normotensive adults, an aqueous extract of KRG root at a mean dose of 610 mg significantly decreased BP at 45, 60, and 75 minutes after intake. 34 Thus, although studies on ginseng and BP exist, the use of extracts and nonrandomized designs was common, which precluded an accurate assessment of efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…NAG is unique from P ginseng, which is the species that has been tested in other clinical interventions on ginseng and BP. 16,[33][34][35] After harvest, the root portion of NAG is dried, whereas the root portion of P ginseng is either dried or steamed, 1 with the steamed form being marketed as Korean red ginseng (KRG). Importantly, NAG contains a 3-to 5-times higher content of ginsenosides and different profile of ginsenosides than both forms of P ginseng.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 However, the Pharmacopoeia of the People's Republic of China recommends dosages of 3 to 9 g of the root as a tea, with higher dosages recommended for more debilitated patients. 22 Several clinical trials [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] (Table 1) have been performed using various doses from 40 to 800 mg of ginseng extract and 2 to 6 g of plant material. 38 In this study, we used a dosage of 800 mg per day to evaluate the safety and tolerability of PG in cancer patients for CRF.…”
Section: Interventionmentioning
confidence: 99%
“…Ginseng has been used in the Asian pharmacopeia as a traditional medicinal plant for treating illness, restoring homeostasis, promoting longevity and, in particular, for controlling cardiovascular disease [26] . Han et al have reported that the oral administration of red ginseng decreases the systolic blood pressure, whereas the authors observed no obvious effect on diastolic blood pressure in essential hypertensive patients [27] . The active components and the underlying mechanisms of ginseng remain unknown.…”
Section: Discussionmentioning
confidence: 98%